THE EFFECTS OF HUMAN DEVELOPMENT INDEX AND INFLATION ON ECONOMIC GROWTH IN SOUTH SUMATRA PROVINCE - Sayyid Muhammad Abdurrahman; M. Fazal Rizvi; Maya Panorama (SEAN Institute, 2023)
This study aims to determine and analyze the effect of the human development index (HDI) and inflation on economic growth in South Sumatra Province. This type of research is quantitative using secondary data obtained from the South Sumatra Central Bureau of Statistics in the 2015-2021 period. The data was analyzed by multiple linear equation analysis with the help of the Eviews 9.0 program. This study analyzes partially that the human development index has a positive and significant effect on economic growth in South Sumatra Province. Inflation partially has a negative and insignificant effect on economic growth in South Sumatra Province. And simultaneously the human development index and inflation have a positive and significant effect on economic growth in South Sumatra Province.